التدخل السوري في لبنان وإشكالیة العلاقة السوریة - اللبنانیة - م.م. محمود عبد الرحمن خلف (College of Education for Women, 2019)
The relation ship between Syria and Lebanon is a distinguished one because of the cultural social geographic and historical common factors. So that, Syria considers that Lebanon has a stratieyical depth for it, especially its conflict with (Israel) does end and parts of its lands still under the occupation of the Zionist thus, any conflict in Lebanon between parties and ethnics groups could be considered an important influence on the bases of the Syrian policy. Moreover the issue of Palestine which is considered the central issue for Syria and Arab as whole. In addition to some of the political movements that happened in the region itself. It could be said that Syrian interference in Lebanon has a positive influence, despite the negative one, it lies in protecting them from being killed on the bases of identity. This helps in reducing the domination of some armed groups. But the point view of the Syrian differs from that of the Lebanese groups, so that Syrian interference lost its validity and thus it should be ended, as a result of the international decision 1559 which demanded Syria to leave Lebanon after security settlement.